DAMPAK EKSPEKTASI DAN VOLATILITAS HARGA PADI TERHADAP ALOKASI LAHAN TANAM PADI DI INDONESIA - Nurhayanti, Yanti; Soetjipto, Widyono (Universitas Muhammadiyah Yogyakarta, 2017)
This paper aims to look at the impact expectations and volatility of the price of rice and corn to the acreage of rice in Indonesia. It is expected that with this paper can contribute academically. BBy using a panel data in district paddy, period 2011-2015, empirically proven expectations rise in price rice may increase the acreage of paddy. The volatility of the price rice paddy decreased acreage of rice.By using a panel data in district paddy, period 2011-2015, empirically proven expectations rise in price rice may increase the acreage of paddy. The volatility of the price rice paddy decreased acreage of rice.y using a panel data in district paddy quarterly period 2011-2015, empirically proven expectations rise in price rice may increase the acreage of rice. Increase the volatility of the price rice can decrease allocation acreage of rice. The estimation results with SYS-GMM method showed any increase in price rice expectations 1% can improve the allocation of planting 0,2500%. The volatility of rice can decrease 0,0051%Â acreage of rice ceteris paribus. While the increase volatility of corn prices can increase the allocation of land for planting rice 0,0049% ceteris paribus. The estimation results also indicate that the allocation of land planting rice more responsive than planting corn land allocation to alter expectations and price volatility. Policy price /HPP for farmers are not guaranteed to improve the allocation of arable land rice in each planting season.